ON THE FUNCTIONAL MORPHOLOGY OF A NEW FAUNA OF MONOGENOIDEA ON FISHES FROM TRIVANDRUM AND ENVIRONS PART V. GEPHYROCOTYLIDAE FAM. NOV - R. VISWANATHAN UNNITHAN (BRIN Publishing (Penerbit BRIN), 1966)
-